1992
DOI: 10.1021/jm00099a020
|View full text |Cite
|
Sign up to set email alerts
|

Orally active, nonpeptide oxytocin antagonists

Abstract: The first nonpeptide antagonists of the neurohypophyseal hormone, oxytocin (OT) are described. Derivatives of the spiroindenepiperidine ring system, these compounds include L-366,509, an orally bioavailable OT antagonist with good in vivo duration. The potential use of these agents for treatment of preterm labor and their significance as new nonpeptide ligands for peptide receptors are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 5 publications
0
41
0
1
Order By: Relevance
“…The spiropiperidine part structure of this compound is a privileged structure in the terminology of Evans et al (11), since it is also found, for example, in oxytocin (15) and sigma receptor ligands (16). We derivatized the spiropiperidine core of 1 and from this approach lead compound 2 was discovered.…”
mentioning
confidence: 99%
“…The spiropiperidine part structure of this compound is a privileged structure in the terminology of Evans et al (11), since it is also found, for example, in oxytocin (15) and sigma receptor ligands (16). We derivatized the spiropiperidine core of 1 and from this approach lead compound 2 was discovered.…”
mentioning
confidence: 99%
“…Spiro compounds are becoming key building blocks for drug discovery as these templates have been shown to exhibit a variety of interesting biological activities, such as growth hormone secretagogues (Ibutamoren, MK-0677) [1], neurokinin antagonists [2], oxytocin antagonists [3], monoamine transporter inhibitors [4], bradykinin antagonists [5] and cell cycle inhibitors [6]. Due to their structure, they interact with a wide range of receptors and this activity has resulted in significant interest in developing efficient methods to prepare spiro compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These nonpeptidyl antagonists are represented by lead structures containing spiroindenylpiperidinecamphor-sulfonamide moieties (3,6,14). Further modification of these structures with potencyenhancing groups led to a group of potent, selective antagonists represented by Compounds I (L-368,899), II, and III ( Fig.…”
Section: Introductionmentioning
confidence: 99%